From the damsel in distress to the distressed dude: Transgressing gender dichotomies in Howl's Moving Castle - Ayyildiz, Nilay Erdem (Peter Lang Publishing Group, 2024)
The chapter aims at analysing English author Diana Wynne Jones's young adult fantasy novel Howl's Moving Castle (1986) against the background of Rosemary Jackson's theory of fantasy. The novel centers on a teenage girl, Sophie, achieving her agency free of the heteronormative social norms, subverting the storyline and characterization of classical European fairy tales, including Cinderella, Snow White, The Sleeping Beauty, Bluebeard and particularly Beauty and the Beast. The study contends that the novel draws a secondary world of magic dismantling the conventions of classical fairy tales based on gender dichotomies including good/evil, beautiful/ugly, young/old, the masculine/feminine, and natural/ step. The chapter intends to scrutinize how the dichotomies communicated through characterization in the widely-read fairy tales are destabilized and transgressed throughout the novel as a critical response to them in light of Rosemary Jackson's theory of fantasy. Jackson presents an illuminating guide to reading the fantastic as a text of subversion facilitating to decipher the political and cultural association of the narrated unreal with the reality. From this standpoint, the Jacksonian reading of Jones's Howl's Moving Castle indicates that Jones's fantasy world contributes to the deconstruction of the Other empowering the othered woman to achieve her subjectivity regardless of her age, appearance, and cultural background. © 2023 Peter Lang Group AG, Lausanne. Published by Peter Lang GmbH, Berlin, Deutschland. All rights reserved.
Keywords: Diana Wynne Jones; Fairy tales; Fantasy; Gender dichotomies; Howl's Moving Castle